Research on the Assembly Pattern of MMC Bolted Flange Joint. (2015) - Zhang, L.Z.; Liu, Y.; Sun, J.C.; Ma, K.; Cai, R.L.; Guan, K.S.
Abstract: In a Metal-to-Metal Contact (MMC) bolted flange joint the stress of sealing surfaces is constant. It canwithstand higherbolt load. So, under the operating conditions of high temperature, high pressure or their fluctuations, the sealing effect of MMC bolted flange joints is better than of floating (FLT) bolted flange joints. According to the structure characteristics of MMC bolted flange joints, a new tightening method (SH-Method) was recommended in this work. The bolt forces during the tightening process of a MMC bolted flange joint with SH-Method were calculated and analyzed with the finite element analysis Software ANSYS. The calculating model and results were experimentally verified. Both calculating and experimentally results showed, the new tightening method 'SH-Method'has the advantages of fewer steps, simpler operation, more uniform bolt force, and better sealing effect, compared to the star pattern and the alternative pattern #3 of ASME PCC-1, in which only the pattern methods for FLT flange joints are recommended.